Correlation between various Measurements of Sternum with Stature - An Autopsy based Study (Medico Legal Update, 2020)
The sternum is of crucial significance while estimating body stature. Dwight, in the late 19th century,discussed potential use of the sternum for estimation of the stature. Various researchers have shown thatthe sternum may be of use in stature assessment merely when long bones are not obtainable. The study wasconducted to analyse the correlation between the stature and various measurements of the sternum. Theposterior curved length, length of manubrium, length of mesosternum and length of sternum were measuredin 300 adult sterna. The mean length of a cadaver (Stature) was observed to be greater in males (162.34± 8.03 cm) as compared to females (156.53 ± 8.50 cm). A positive moderate correlation (R ranging from0.332 to 0.647) was observed between various measurements of sternum with stature in both the genders.Sternal length shall be considered as a better parameter over other sternal measurements for estimating thestature. However the application for utilizing the sternum for stature estimation should be restricted to thepopulation sample for and from which they have been developed.